2023
DOI: 10.1002/chem.202301012
|View full text |Cite
|
Sign up to set email alerts
|

Smart Temperature‐Gating and Ion Conductivity Control of Grafted Anodic Aluminum Oxide Membranes

Abstract: Over the past few decades, stimuli-responsive materials have been widely applied to porous surfaces. Permeability and conductivity control of ions confined in nanochannels modified with stimuli-responsive materials, however, have been less investigated. In this work, the permeability and conductivity control of ions confined in nanochannels of anodic aluminum oxide (AAO) templates modified with thermo-responsive poly(N-isopropylacrylamide) (PNIPAM) brushes are demonstrated. By surface-initiated atom transfer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, the thermo-responsive switching of the gates was preserved for three consecutive closed-opened cycles. Very recently, Lee et al 96 reported for a similarly prepared AAO- g -pNIPAM membrane a decrease in resistance with increasing temperature due to the positive gating effect.…”
Section: Functionalized Porous Support Membranesmentioning
confidence: 98%
“…Moreover, the thermo-responsive switching of the gates was preserved for three consecutive closed-opened cycles. Very recently, Lee et al 96 reported for a similarly prepared AAO- g -pNIPAM membrane a decrease in resistance with increasing temperature due to the positive gating effect.…”
Section: Functionalized Porous Support Membranesmentioning
confidence: 98%
“…In recent decades, nanoporous membranes have emerged as versatile platforms with applications across various fields, including biomedical sensing, , nanofiltration, energy conversion, and smart separation and gating. The nanoporous membranes, exhibiting high performance and versatility, usually feature well-controlled nanopore geometries and advanced materials with excellent functionality. ,, Achieving both of these two key characteristics simultaneously often involves surface modification of nanoporous membranes using functional polymer materials, which proves to be a powerful and effective strategy. Numerous surface modification methods with polymers have been developed based on various interfacial interactions. For example, a simple deposition method is frequently utilized to modify nanoporous membranes by dip or spin coating using polymer solutions, capitalizing on physical interfacial bonding, such as van der Waals forces or hydrogen bonding. , The layer-by-layer assembly method has also been employed for membrane modification through electrostatic interactions with charged polymers. , Additionally, the surface-initiated polymerization method has been introduced to modify membranes with high-grafting density and homogeneous polymer brushes through covalent bonding. These mentioned traditional surface modification methods, however, usually suffer from issues such as weak bonding, the need for specialized polymer and membrane materials, or complex polymer synthesis techniques, which can limit their applicability for long-lasting usage and mass production development.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nanoporous membranes have emerged as versatile platforms with applications across various fields, including biomedical sensing, 1 , 2 nanofiltration, 3 5 energy conversion, 6 8 and smart separation and gating. 9 11 The nanoporous membranes, exhibiting high performance and versatility, usually feature well-controlled nanopore geometries and advanced materials with excellent functionality. 8 , 12 , 13 Achieving both of these two key characteristics simultaneously often involves surface modification of nanoporous membranes using functional polymer materials, which proves to be a powerful and effective strategy.…”
Section: Introductionmentioning
confidence: 99%